ON THE OBSERVED PHYSICAL PROPERTIES AND EVOLUTIONARY TRENDS OF HOT SUBDWARFS IN BINARY SYSTEMS - Pustylnik, I. (Одеські астрономічні публікації, 2017)
In our brief review we summarize the latest advances in studies of white dwarfs both as single objects and the components of binary systems. We discuss the observed properties of the hot subdwarfs (sdws), the various techniques of their discovery and some peculiarities of their evolution following the final stages of AGB, both for single stars and binary cores of PN. We find that the observed statistics of sdws clearly point to drastically different evolutionary histories for sdws belonging to very wide pairs and those found in close binaries.